Continuous flow (Sulfated) Zirconia Catalysed Cascade Conversion of Levulinic Acid to γ‐Valerolactone. Issue 3 (13th January 2023) - Merenda, Andrea; Orr, Samantha A.; Liu, Yang; Hernández Garcia, Blanca; Osatiashtiani, Amin; Morales, Gabriel; Paniagua, Marta; Melero, Juan A.; Lee, Adam F.; Wilson, Karen
Abstract: γ‐Valerolactone (GVL) is a renewable and versatile platform chemical derived from sustainable carbon feedstocks. The cascade conversion of levulinic acid into GVL requires Brønsted and Lewis acid catalysed reactions. Here, a dual‐catalyst bed configuration is demonstrated that promotes synergy between Brønsted acid sites in sulfated zirconia (SZ) and Lewis acid sites in ZrO2 /SBA‐15 for the liquid phase, continuous flow esterification and subsequent catalytic transfer hydrogenation (CTH) of levulinic acid to GVL. A saturated surface sulfate monolayer, possessing a high density of strong Brønsted acid sites, was optimal for levulinic acid esterification to isopropyl levulinate over SZ (>80 % conversion). A conformal ZrO2 bilayer, deposited over a SBA‐15 mesoporous silica and possessing mixed Brønsted:Lewis acidity, catalysed CTH of the levulinate ester and subsequent dealcoholisation/cyclisation to GVL (>60 % selectivity). Maximum stable productivity for the dual‐bed was 2.2 mmolGVL .gcat .h −1 at 150 °C, significantly outperforming either catalyst alone or a physical mixture of both. Flow chemistry is a versatile approach to achieve spatial control over cascade transformations involving distinct catalytically active sites. Abstract : Transforming bio‐derived molecules into value added products often requires multiple chemical reactions driven by different catalytic active sites. It remains challenging to design catalysts to drive such chemical 'cascades' in a single reactor. Here, the synergistic coupling of different catalysts, placed within spatially separated reactors, is demonstrated for the cascade conversion of levulinic acid to γ‐valerolectone in continuous flow.